RELATIONSHIP OF EPICARDIAL ADIPOSE TISSUE THICKNESS AND NEUTROPHIL TO LYMPHOCYTE RATIO WITH CORONARY LESION SEVERITY IN STABLE CORONARY HEART DISEASE - Darwin Indra; Lucia Panda; Edmond Jim; Dewi U. Djafar; Victor G. X. Rooroh; Monique P. F. Rotty (JURNAL WIDYA MEDIKA, 2022)
Introduction: Stable angina pectoris (SAP) is the one of the leading causes of death in men and women from every major ethnic group. Several studies have shown that the neutrophil to lymphocyte ratio (NLR) is a systemic inflammatory marker associated with cardiovascular events. EAT has been considered to have an important role in cardiovascular physiology and pathogenesis. This study aimed to investigate the relationship of EAT thickness and NLR with coronary lesion severity in patients with stable coronary heart disease. Methods: This study was a cross-sectional study conducted at Department of Cardiology and Vascular of Kandou General Hospital, Manado, North Sulawesi, Indonesia, from May to August 2019. The population were patients with SAP who underwent coronary angiography procedures. The relationship between the EAT and NLR and the SYNTAX score were evaluated on a bivariate and multivariate level. Results: A significant linear relationship between EAT thickness and SYNTAX score was found (Pearson r = 0.32; p = 0.014). In addition, after controlling for sex and NLR, the correlation between EAT thickness and SYNTAX score increased to almost 0.7 points for each millimeter increase in EAT (95% CI 3.45 - 10.25; p